Experimental factorial design on hydroesterification of waste cooking oil by subcritical conditions for biodiesel production - dos Santos, Letícia Karen [UNESP]; Hatanaka, Rafael Rodrigues [UNESP]; de Oliveira, José Eduardo [UNESP]; Flumignan, Danilo Luiz [UNESP] (Elsevier, 2017)
Hydroesterification is innovation biodiesel production using low cost feedstock by two-step: hydrolysis of waste cooking oil to FFAs in subcritical water and chemical esterification of FFAs into FAME (biodiesel) with methanol. The purpose was to apply the experimental factorial design to evaluate the influence of reaction variables on the effectiveness of hydrolysis and determine the relationship of FFAs and FAMEs yields. Experiments were conducted in a batch reactor under diverse reaction conditions to determine the optimal parameters for hydrolysis. This analyses indicated that high FFAs yields (95 wt%) are achieved using 250 °C; 120 min; 100:1 water-to-oil molar ratio and 700 rpm. Research results revealed a conversion the FFAs in 98.5 wt% of FAMEs with high quality by esterification in biodiesel production. This study shows that the biodiesel produced by subcritical/chemical hydroesterification process has similar qualities to the biodiesel obtained by traditional alkaline transesterification, which suggests a promising alternative for biodiesel production.
Keywords: Biodiesel; Free fatty acids; Hydroesterification; Optimization; Response surface analyses; Waste cooking oil